Millimeter-wave microstrip antenna with enhanced gain for dual-band 26 /29 GHz operation - Ali, Neksad; Islam, Abu Zafor Muhammad Touhidul (ASCEE, 2025)
This paper suggests a dual-band rectangular patch antenna design and presents analysis of the radiation performance metrics for its operation and application in the 26 and 29 GHz millimeter-wave 5G mobile communication. To achieve antenna’s hign gain and improved radiation performance, the design includes a rectangular loop and two L-sloted patch and defective ground structure (DSG). The antenna is excited using 50 Ω inset feed line and modeled in CST Studio Suite. The simulation results show that the designed small sized 22.5×18.5 mm2 antenna offers improved super high gain of 9 dB and 11.39 dB and directivity of 9.49 dBi and 12.06 dBi at 26 and 29 GHz mmWave bands. Moreover, the antenna offers minimum reflection coefficient, acceptable VSWR and very good efficiency of 94.83% at 26 GHz, whilst of 94.44% at 29GHz, respectively. These findings along with its compact design suggest that the projected patch antenna would be a be a good choice for the development of high gain dual-band antenna for 5G mmWave mobile systems